Psychoneuroimmunology. Vol. 1 - Ader, Robert; Felten, David L.; Cohen, Nicholas (Academic press, 2001)
This current edition of Psychoneuroimmunology reflects an increasing sophistication and a very considerable expansion of the research and the researchers who are now devoting attention to what has become a fully accepted interdisciplinary field of research. Neural and neuroendocrine effects on immune processes are the subjects of the opening sections of this volume. Several of these chapters are substantive updates or more detailed additions to material presented in the second edition of Psychoneuroimmunology necessitated by the progress that has been made in elaborating the nature of neural-immune interactions. Other chapters, such as those describing the phylogenetic history of neural-immune interactions, biological rhythms in immune function, or the role of sleep or fever in immunity and health, have not been covered in previous editions. Immune system effects on the nervous system, the central and peripheral action of cytokines on neural, neuroendocrine, and immunologic processes and on behavior, are described in the entirely new third section of the book.